Conceptus interferon gamma is essential for establishment of pregnancy in the pig. Issue 6 (5th October 2021) - Johns, Destiny N; Lucas, Caroline G; Pfeiffer, Caroline A; Chen, Paula R; Meyer, Ashley E; Perry, Shelbi D; Spate, Lee D; Cecil, Raissa F; Fudge, Melissa A; Samuel, Melissa S; Spinka, Christine M; Liu, Hongyu; et al.
Abstract: Establishment and maintenance of pregnancy in the pig is a complex process that relies on conceptus regulation of the maternal proinflammatory response to endometrial attachment. Following elongation, pig conceptuses secrete interferon gamma ( IFNG ) during attachment to the endometrial luminal epithelium. The objective here was to determine if conceptus production of IFNG is important for early development and establishment of pregnancy. CRISPR/Cas9 gene editing and somatic cell nuclear transfer technologies were used to create an IFNG loss-of-function study in pigs. Wild-type ( IFNG +/+ ) and null ( IFNG −/− ) fibroblast cells were used to create embryos through somatic cell nuclear transfer. IFNG expression was not detected in IFNG −/− conceptuses on either day 15 or day 17 of pregnancy. Ablation of conceptus IFNG production resulted in the reduction of stromal CD3 + and mast cells, which localized to the site of conceptus attachment on day 15. The uteri of recipients with IFNG −/− conceptuses were inflamed, hyperemic and there was an abundance of erythrocytes in the uterine lumen associated with the degenerating conceptuses. The endometrial stromal extracellular matrix was altered in the IFNG −/− embryo pregnancies and there was an increased endometrial mRNA levels for collagen XVII ( COL17A1 ), matrilin 1 ( MATN1 ), secreted phosphoprotein 1 ( SPP1 ), and cysteine-rich secretory protein 3 ( CRISP3 ), which are involved with repair and remodeling of the extracellular matrix. These results indicate conceptus IFNG production is essential in modulating the endometrial proinflammatory response for conceptus attachment and survival in pigs. Abstract : Ablation of IFNG in the pig conceptus causes conceptus degeneration and endometrial inflammation.